Hawtrey, austerity, and the "Treasury view", 1918-25 - Clara Elisabetta Mattei (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
In Great Britain the seven years following WWI were marked by rigorous austerity policies. From 1918 to 1925 the main objectives were budget cuts and monetary deflation. Certainly, being the central department for financial policies, the British Treasury had decisive authority in setting such economic agenda. In particular, the official who had the greatest weight with chancellors of the Exchequer was the Controller of Finance, Basil P. Blackett (1917-1922), followed by Sir Otto Niemeyer (1922-1927). Their papers in the Treasury files reveal that the economist Ralph Hawtrey was the primary source of economic knowledge for Blackett and especially for Niemeyer. This work proves that Hawtrey's original economic theory provided solid theoretical justifications for the austerity policies. Hawtrian economics refined and strengthened the economic stance of the senior officials of the British Treasury. This study draws on Hawtrey's most important scientific works together with his press articles and copious Treasury papers to unravel the conceptual building blocks of Hawtrey's austerity doctrine. It emerges that his policy prescriptions ensued directly from his economic model. Hawtrey advocated monetary stabilization through the management of the bank rate, budgetary rigor, and rejection of public investment, all of which became widely established goals among other orthodox economic institutions, from the Bank of England to the League of Nations. This paper reveals that, in the early post WWI years, economic theory had clear operative force on policymaking.
Keywords: N44; N14; B13; B 41; 330; Ralph Hawtrey; Austerity; Treasury View; Interwar Years; Deflation; Savings